SAMOS air‐sea fluxes: 2005–2014. (8th June 2016) - Smith, S. R.; Lopez, N.; Bourassa, M. A.
Abstract : Bulk turbulent heat and momentum fluxes are derived using 1‐minute interval data collected by the Shipboard Automated Meteorological and Oceanographic System (SAMOS) initiative. The fluxes are provided along cruise track lines for individual research vessels (RVs) and are derived using three widely accepted air‐sea flux algorithms. SAMOS data collected by 19 RVs between 2005 and 2014 are used to create the dataset. The data are concentrated in the oceans around North America, but select data are available from most ocean basins.